(untitled) (Revista Puertorriqueña de Psicologia, 2019)
The Association of Virgin Islands Psychologists (AVIP) under the auspices of the Caribbean Alliance of National Psychological Associations (CANPA) supported by the Union of Psychological Sciences (IUPsyS) and the American Psychological Association (APA) is delighted to invite you to the FIFTH Caribbean Regional Conference of Psychology, to be held November 17- 20, 2020 in St. Croix in the US Virgin Islands.